Prospective Cross-Sectional Study of the Prevalence of Incidental Pancreatic Cysts During Routine Outpatient Endoscopic Ultrasound. Issue 7 (October 2015) - Sey, Michael Sai Lai; Teagarden, Sean; Settles, Diane; McGreevy, Kathleen; Coté, Gregory A.; Sherman, Stuart; McHenry, Lee; LeBlanc, Julia K.; Al-Haddad, Mohammad; DeWitt, John M.
Abstract : Objective: Incidental pancreatic cysts are often detected during abdominal imaging and require follow-up since some have malignant potential. Endoscopic ultrasound (EUS) is highly sensitive for pancreatic diseases, yet the prevalence of incidental pancreatic cysts discovered with EUS is unknown. The objective of the study was to determine its prevalence by EUS. Methods: A prospective cross-sectional study was conducted. Patients undergoing EUS for nonpancreatic indications and without known pancreatic abnormality were recruited to assess the prevalence of pancreatic cysts and its characteristics. Risk factors were determined by logistic regression. Results: We enrolled 341 patients (mean age, 59 years; 187 females) and found 46 incidental pancreatic cysts (median [range], 5 [2–80] mm) in 32 patients (9.4%). Branch duct intraductal papillary mucinous neoplasm was the most common finding. Seven cysts were larger than 1 cm and 1 adenocarcinoma was discovered. Multivariate logistic regression showed an association between pancreatic cysts and older age (odds ratio, 1.04 per year; 95% confidence interval, 1.01–1.08) and female sex (odds ratio, 3.08; 95% confidence interval, 1.25–7.45). Conclusions: In our population, the prevalence of incidental pancreatic cyst discovered on EUS was 9.4% and the majority were less than 1 cm. Increasing age and female sex were associated with the development of pancreatic cysts.